Characterisation of Nesoia latifolia (Halymeniaceae, Rhodophyta) from Europe with emphasis on cystocarp development and description of Nesoia mediterranea sp. nov. Issue 4 (4th July 2019) - Rodríguez-Prieto, Conxi; De Clerck, Olivier; Huisman, John M.; Lin, Showe-Mei
ABSTRACT: Halymenia latifolia from Atlantic Europe and the Mediterranean Sea has been shown in previous studies to be a distinct evolutionary clade, separate from the Halymenia clade that includes the generitype. Halymenia latifolia has recently been transferred to the genus Nesoia . Phylogenetic analyses based on rbc L sequences of European (Atlantic and Mediterranean) specimens of putative N. latifolia showed that two species were present, one representing an undescribed species ( Nesoia mediterranea sp. nov .) and one corresponding to genuine N. latifolia . In order to establish morphological taxonomic characteristics that distinguish these two cryptic species, we examined and described their reproductive structures and postfertilisation stages. In addition, our results showed that the development of the carpogonial branch ampullae pre- and postfertilisation can be used to separate Nesoia from Halymenia, because the basal nutritive cell cluster found in Halymenia is lacking in Nesoia . Other lesser known species currently placed in the genus Halymenia from Atlantic Europe and the Mediterranean Sea require molecular characterisation and examination of their reproductive morphology as part of further revision of the genus.